2015
DOI: 10.1099/vir.0.000184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of porcine epidemic diarrhoea virus recovered from a full-length infectious cDNA clone

Abstract: Porcine epidemic diarrhoea virus (PEDV) causes acute diarrhoea and dehydration in swine of all ages, with significant mortality in neonatal pigs. The recent rise of PEDV outbreaks in Asia and North America warrants an urgent search for effective vaccines. However, PEDV vaccine research has been hampered by difficulties in isolating and propagating the virus in mammalian cells, thereby complicating the recovery of infectious PEDV using a full-length infectious clone. Here, we engineered VeroE6 cells to stably e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 55 publications
4
87
0
Order By: Relevance
“…In 2013, Li et al first reported a reverse genetics system for the Korean classical PEDV vaccine strain DR13 based on a targeted RNA recombination method (Li et al, 2013). Following this, Jengarn et al engineered an infectious cDNA clone of the Thailand classical PEDV strain AVCT12 into a bacterial artificial chromosome (BAC) using eight contiguous cDNA fragments (Jengarn et al, 2015). In 2016, Beall et al constructed infectious cDNA clones of a highly pathogenic US PEDV strain PC22A using in vitro ligation of contiguous cDNA fragments, and performed in vitro transcription to generate infectious viral RNA (Beall et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Li et al first reported a reverse genetics system for the Korean classical PEDV vaccine strain DR13 based on a targeted RNA recombination method (Li et al, 2013). Following this, Jengarn et al engineered an infectious cDNA clone of the Thailand classical PEDV strain AVCT12 into a bacterial artificial chromosome (BAC) using eight contiguous cDNA fragments (Jengarn et al, 2015). In 2016, Beall et al constructed infectious cDNA clones of a highly pathogenic US PEDV strain PC22A using in vitro ligation of contiguous cDNA fragments, and performed in vitro transcription to generate infectious viral RNA (Beall et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This isolate most likely grows in vivo in gnotobiotic piglets, as animals seroconverted after inoculation (Lin et al, 2015b), but its virulence remains to be determined.It has been shown that during the generation of live attenuated vaccines for PEDV by passing the virus in Vero cells, in the case of both the Korean DR13strain and the Japanese P-5V attenuated viruses included a protein 3 in which more than half of the carboxyterminal domain was deleted . Similarly, while a recombinant virus lacking ORF3 expression could be rescued, when ORF3 was restored the recombinant virus could not be rescued (Jengarn et al, 2015). Therefore, it seems that protein 3 could have a role in vivo and that its total or partial deletion helps to maintain PEDV in Vero cells.…”
Section: Isolation Of Field Strains Of Pedv In Cellmentioning
confidence: 92%
“…Âî âðåìÿ âñïûøêè âèðóñíîé èíôåêöèè ïðåîáëàäàþùèì íàïðàâëåíèåì âåòðà â òå÷åíèå ìåñÿöà áûëî ñåâåðíîå. Èíîãäà âåòðû äóëè â þãî-çàïàäíîì (Jengarn et al, 2015). Although PEDV is in general propagated in Vero cells, it efficiently infects a variety of cell types, including porcine intestinal epithelial cells (IECs) (Zhao et al, 2014)or human Huh 7 cells (Liu et al, 2015).…”
Section: ïåðåäà×à Pedv: ðàñïðîñòðàíåíèå âèðóñàmentioning
confidence: 99%
See 1 more Smart Citation
“…The first CoV infectious cDNA clone was obtained for TGEV, as a bacterial artificial chromosome (BAC) (Almazan et al, 2000). Since then, additional cDNA clones were obtained for TGEV and PEDV, based either on BACs or in vitro ligation (Almazan et al, 2014; Beall et al, 2016; Jengarn et al, 2015). This review will focus on the study of enteric CoVs interaction with the host to determine virulence genes, since the modification or deletion of these genes may lead to virus attenuation, and to the generation of vaccine candidates to prevent infection by porcine CoVs.…”
Section: Introductionmentioning
confidence: 99%